Teaching that changes lives 12 mindset tools for igniting the love of learning - Adams, Marilee (Berrett-Koehler Publishers, 2013)
"Building on the success of her classic, bestselling book, Change Your Questions, Change Your Life (over 100,000 copies sold), Marilee Adams shows in this new book how teachers and other education professionals can change their own and their students' lives by developing an active, inquiring mindset and igniting a lifelong love of learning"--